Intraoperative and postoperative short-term outcomes of intracorporeal anastomosis versus extracorporeal anastomosis in laparoscopic right hemicolectomy - Zhou, Yuhang; Zhou, Yuchen; Wang, Chuandong; Ye, Rong; Lin, Xiaojun; Tan, Song; Chen, Weijie; Mi, Yulong; Yang, Changshun; Lin, Shengtao; Li, Weihua (Frontiers in Oncology, 2023)
Background Intracorporeal anastomosis (IA) is a difficult but popular anastomotic approach for reconstruction of digestive tract after laparoscopic right hemicolectomy, which may reduce some limitations faced during extracorporeal anastomosis (EA). Methods A retrospective review of 78 patients who underwent laparoscopic right hemicolectomy by a veteran surgeon in a high-volume public tertiary hospital, including 50 patients with IA and 28 patients with EA. The intraoperative-related factors and short-term results of the two anastomotic approaches were compared. Results There was no significant difference in demographics and clinical characteristics between the two groups (P>0.05). The intraoperative blood loss was less (P=0.010) and the incision length was shorter (P<0.001) in the intracorporeal group. Postoperative farting time was faster (P=0.005) and postoperative pain score (VAS) was lower (P<0.001) in IA group. Although the anastomotic time of IA was shorter (P<0.001), the operative time of the two groups were similar. And number of lymph nodes harvested, NLR from POD1 to POD3, postoperative hospital stay and overall hospital stay between the two groups were comparable. Except for significant difference in abdominal infection rate, the Clavien-Dindo classification and the incidence of other postoperative complications were not statistically different. Moreover, the morbidity of abdominal infection decreased with time in the IA group (P=0.040). Conclusion IA is a reliable and feasible procedure, which has faster anastomotic time, earlier return of bowel function and superior postoperative comfort of patient, compared to EA. The postoperative complication rate of IA is similar to that of EA, and may be improved with the IA technical maturity of surgeons, which potentially contributes to the development of ERAS.